Analysis of early stage osteonecrosis of the human femoral head and the mechanism of femoral head collapse - Wang, Cheng (Int J Biol Sci, 2018)
We explored the mechanism of early stage osteonecrotic femoral head collapse by analyzing and comparing different regions in human osteonecrotic femoral head samples. Eight osteonecrotic femoral heads (ARCO II-III) were obtained from patients undergoing total hip arthroplasty. Bone structure was observed and evaluated by micro-computed tomography (CT) scans and pathology. Osteoblast and osteoclast activities were detected by tartrate-resistant acid phosphatase, alkaline phosphatase, and immunofluorescent staining. Some trabeculae had microfractures in the subchondral bone and necrotic region, which had lower bone mineral density, as well as trabecular thickness and number, but greater osteoclast activity. A sclerotic band had already appeared in certain samples which had greater trabecular thickness and number, bone mineral density, and osteoblast activity. The appearance of the femoral head did not change significantly in the early stage of osteonecrosis of the femoral head. However, osteoblast and osteoclast activities had already changed in different regions of the osteonecrotic femoral head, which may lead to eventual collapse of the femoral head. Therefore, osteonecrosis of the femoral head must be treated during the early stage. In addition, osteoblast activity should be promoted and osteoclast activity inhibited as early as possible to prevent collapse of an osteonecrotic femoral head.